ANALISIS REGRESI KEGAGALAN PROPORSIONAL DARI COX PADA DATA WAKTU TUNGGU SARJANA DENGAN SENSOR TIPE I (Studi Kasus di Fakultas Sains dan Matematika Universitas Diponegoro) - Oka Afranda; Triastuti Wuryandari; Dwi Ispriyanti (Jurnal Gaussian, 2015)
One of the goals of studying in Higher Education Institutionis to obtain a job as soon as possible. A graduate is not required to be an unemployed. In Indonesia, the average period of waiting time for undergraduate (S1) to get the first job is 0 (zero) to 9 (nine) months. There are several factors have influenced the length of an undergraduate to get a job. They are Grade Point Average (GPA), Length of Study, etc. Therefore, it is important to know the factors influencing the waiting time of undergraduates to get a job. One method that can be used is the analysis of survival. Survival analysis is the analysis of survival time data from the initial time of the study until certain events occur. One method of survival analysis is Cox Proportional Hazard Regression. It is used to determine the relationship between one or more independent variables and the dependent variable. Cases raised in this study were the factors influencing the waiting time of graduates of the Faculty of Science and Mathematics, University of Diponegoro by using Type I data censoring. The conclusions state that the factors influencing the waiting time of graduates are Organization, Department, and Gender.Keywords:        Waiting time of undergraduate, survival analysis, Cox Proportional Hazard, Regression, University of Diponegoro.